The Convention on Biological Diversity and Protected Natural Territories: Environmental Law Aspects - Penchev, Georgi (Research Papers, 2022)
Basic aim of this study is analysis of the UN Convention on Biological Diversity and protocols to it in the light of its meaning for the protected natural territories. The basic task of the study consists in consideration of the legal measures, regulated in respective international agreements and their introduction in the Bulgarian environmental legislation. The comparative law and formal-logical methods of scientific research are used. The result of study is related to formulation of general conclusions from considered international law regulation and suggestions for its improvement.
Keywords: Protected natural territories; Biological diversity; Convention